Catalysis by materials with well-defined structures - Wu, Zili; Overbury, Steven H. (Elsevier Ltd., 2015)
Catalysis by Materials with Well-Defined Structures examines the latest developments in the use of model systems in fundamental catalytic science. A team of prominent experts provides authoritative, first-hand information, helping readers better understand heterogeneous catalysis by utilizing model catalysts based on uniformly nanostructured materials. The text addresses topics and issues related to material synthesis, characterization, catalytic reactions, surface chemistry, mechanism, and theoretical modeling, and features a comprehensive review of recent advances in catalytic studies on nanomaterials with well-defined structures, including nanoshaped metals and metal oxides, nanoclusters, and single sites in the areas of heterogeneous thermal catalysis, photocatalysis, and electrocatalysis. Users will find this book to be an invaluable, authoritative source of information for both the surface scientist and the catalysis practitioner.